Поняття етичних основ процесу доказування у кримінальному судочинстві - Гуртієва, Людмила Миколаївна; Гуртиева, Людмила Николаевна; Gurtieva, Ljudmila (Одеса : Юрид. л-ра, 2012)
In article reflect the complex of theoretical questions, related to research of the ethical bases proof in criminal proceedings. The author express his view-point on definition concept of the ethical bases proof in criminal proceedings. The concept of the ethical bases proof is defined as a system of conventional morality values, principles, and based on their moral norms, moral persuasion subject's proofing. Ethical bases and legal norms are warranty activity on taking, verification and valuation of evidence.
Гуртієва Л. M. Поняття етичних основ процесу доказування у кримінальному судочинстві / Л. M. Гуртієва // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 578-584.
Keywords: етичні основи процесу доказування; моральність; мораль; этические основы процесса доказывания; нравственность; ethical bases proof in criminal proceedings; morality; moral